Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada Lala Studio & Salon Ciseeng Bogor - Solihin, Dede; Oktavianti, Fauziah; Manik, Cornelia Dumarya (Universitas Pamulang, 2024)
Purpose. This study aims to determine the effect of service quality and price on consumer satisfaction at Lala Studio & Salon Ciseeng Bogor. The method used is a quantitative method.. Methods. This study uses quantitative. The population in this study were consumers of Lala Studio & Salon Ciseeng Bogor with a total of 1031 people. The sampling technique used was probability sampling, the sampling method using the slovin formula. The research sample was 289 respondents. The data obtained were analyzed using the Structural Equatin Model Partial Least Square (PLS) technique. Findings. Service quality has a positive and significant influence on consumer satisfaction with the path coefficient value showing that the T-Statistics 8.304 is greater than the T table (1.96) and ρvalue 0.000 and has an original sample value of 0.471. Price has a positive and significant influence on consumer satisfaction with the path coefficient value showing that the T-Statistics 8.304 is greater than the T table (1.96) and ρvalue 0.000 and has an original sample value of 0.375. Implication. Quality of service and price that meets consumer expectations can strengthen the brand image of Lala Studio & Salon in the market. Having a reputation as a studio and salon that offers quality services at a reasonable price can differentiate Lala Studio & Salon from competitors and attract more customers.